Repurposing of Bromocriptine for Cancer Therapy - Seo, Ean-Jeong; Sugimoto, Yoshikazu; Greten, Henry Johannes; Efferth, Thomas (Frontiers in Pharmacology, 2018)
Bromocriptine is an ergot alkaloid and dopamine D2 receptor agonist used to treat Parkinson´s disease, acromegaly, hyperprolactinemia and galactorrhoea, and more recently diabetes mellitus. The drug is also active against pituitary hormone-dependent tumors (prolactinomas and growth-hormone producing adenomas). We investigated, whether bromocriptine also inhibits hormone-independent and multidrug-resistant (MDR) tumors. We found that bromocriptine was cytotoxic towards drug-sensitive CCRF-CEM, multidrug-resistant CEM/ADR5000 leukemic cells as well as wild-type or multidrug-resistant ABCB5-transfected HEK293 cell lines, but not sensitive or BCRP-transfected multidrug-resistant MDA-MB-231 breast cancer cells. Bromocriptine strongly bound to NF-ĸB pathway proteins as shown by molecular docking and interacted more strongly with DNA-bound NF-ĸB than free NF-ĸB, indicating that bromocriptine may inhibit NF-ĸB binding to DNA. Furthermore, bromocriptine decreased NF-ĸB activity by a SEAP-driven NF-ĸB reporter cell assay. The expression of MDR-conferring ABC-transporters (ABCB1, ABCB5, ABCC1, ABCG2) and other resistance-mediating factors (EGFR, mutated TP53, IκB) did not correlate with cellular response to bromocriptine in a panel of 60 NCI cell lines. There was no correlation between cellular response to bromocriptine and anticancer drugs usually involved in MDR (e.g. anthracyclines, Vinca alkaloids, taxanes, epipodophyllotoxins and others). COMPARE analysis of microarray-based mRNA expression in these cell lines revealed that genes from various functional groups such as ribosomal proteins, transcription, translation, DNA repair, DNA damage, protein folding, mitochondrial respiratory chain and chemokines correlated with cellular response to bromocriptine. Our results indicate that bromocriptine inhibited drug-resistant tumor cells with different resistance mechanisms in a hormone-independent manner. As refractory and otherwise drug-resistant tumors represent a major challenge to successful cancer chemotherapy, bromocriptine may be considered for repurposing in cancer therapy.